Penerapan Strategi Pemecahan Masalah Sistematis (Systematic Approach to Problem Solving) untuk Meningkatkan Hasil Belajar Matematika Kelas XI IPS 2 SMA Negeri 1 Kerinci Tahun Pelajaran 2019/2020 - Hadiawati Hadiawati (Universitas Batanghari Jambi, 2020)
This study was an Action Research which was conducted because the student’s achievement on Mathematics were still lower than The Minimum Achievement Criteria (KKM). The research was conducted to see whether the Systematic Problem Solving Strategy could improve the student’s learning achievement. The aim of the research was to improve the student’s comprehension on Algebra Limit Function subject In Mathematics, so their learning achievement also improved significantly. The research participants were the students of grade XI IPS 2 SMAN 1 Kerinci. The researcher was helped by a collaborator who was a Math Teacher at the same school. The study was done in two cycles with four stages, (a) Planning (b) Action (c) Observation (d) Reflection. The result of data analysis showed that the student’s average score in cycle 1 was 69 (65%). It became higher in cyle 2 to 83 ( 85%). There was significant improvement seen from the result of cycle 1 compared to cycle 2. It could be concluded that the implementation of Systematic Problem Solving Strategy on Algebra Limit Function subject improved the student’s learning achievement significantly. Therefore, it was suggested to Math Teachers to apply the strategy in teaching as the alternative solution particularly in Algebra Limit Function subject